Professional responses to 'parental alienation': research-informed practice. Issue 1 (2nd January 2020) - Doughty, Julie; Maxwell, Nina; Slater, Tom
ABSTRACT: Parental alienation was historically a term rejected by courts in England and Wales, but lawyers and social workers have noted an increase in the incidence of its use, possibly driven by campaign groups and media narratives. The two statutory services that provide independent social work advice to courts in England and Wales, respectively, on children's best interests in parenting disputes, have taken different approaches to developing practice guidance in response to concerns about the recent use of alienation terminology. A review of international research and domestic case law was undertaken as part of the development of guidance in Wales. This review revealed a dearth of reliable evidence on the concept of parental alienation, its prevalence, effects and measures for intervention. This article builds on that review and recent developments to discuss the progress being made in practice to counter myths about alienation and considers how best to support practitioners in resisting pressures to conform to these powerful narratives.